FACTORS OF TOURIST PERCEIVED VALUE OF INDONESIA SHOPPING TOURISM - Filda Rahmiati; Grace Amin (President University, 2019)
Shopping becomes a relevant component. Shopping has become a factor that influences the choice of destination, travel, travel and travel. With the desire to develop, it is an interesting phenomenon for policy makers, academics and business leaders around the world. The city of Bandung, as one of the cities called